Goal Setting and Job Enrichment: An Integrated Approach to Job Design - Umstot, Denis D.; Mitchell, Terence R.; Bell, Cecil H. (Academy of Management Review, 1978)
Productivity and job satisfaction are two dominant concerns of managers. One approach to designing jobs so that both of these outcomes can result is to combine job enrichment and goal setting, but little is known concerning the interaction between these two major techniques. This article reviews the empirical literature relating task goals and job enrichment. The interaction of job characteristics, individual differences, and organizational characteristics is reviewed, and an integrated model presented that explains the relationships.